An Experimental Investigation of Clean Syngas Production from Waste Biomass by Gasification Method - DANİŞMAZ, Merdin and DEMİRTAŞ, Cevdet (International Journal of Computational and Experimental Science and Engineering, 2024)
Gasification technology is crucial for the efficient utilization of biomass and coal at high efficiency. Improved processes and systems are necessary to produce synthesis gas from biomass and coal (especially low calorific coals), making the process more advanced and effective. This study focuses on the direct use of waste biomass and low-calorific coals for heating and cooking to obtain synthesis gas with high calorific value. Biomass is examined for direct gasification and conversion into pellet fuel for gasification, and its use in heating and cooking systems are explored. Gas quality is enhanced in gasification stages like drying, pyrolysis, oxidation, and reduction by maintaining the reactor filled with gas and providing synthesis gas supplementation from the pyrolysis zone. Gas cleaning and conditioning processes, treated as separate operations, are carried out within the designed pilot system in a single device, generating ready-to-use gas at the outlet. A valve system that provides downflow for biomass and upflow for coal is developed to enable both to be processed in the same device. Consequently, a system was created that offers more comfortable use and high efficiency in gas production compared to direct combustion, especially in rural areas, where heating and cooking are provided through a single device.